LEGAL PROTECTION ON CHILDREN AS A VICTIMS OF SEXUAL VIOLENCE BASED ON PROGRESSIVE LAW - etik purwaningsih (UNISSULA, 2017)
Sexual violence happened to children are often occurred, after the emergence of sexual cases in Jakarta International School (JIS). It began to arise attention to child victims of sexual violence. This paper aims to provide a review of the protection on child victims of sexual violence at this time. With the sociological juridical method, the primary data were obtained from direct interviews with law enforcement officers, while secondary data were obtained from literature references. The result shows that the legal protection does not pay attention on children as victim. The legal protection for children as victim sexual violence is expected to give punishment to the criminals in the form of payment of compensation to the victim whose amount is determined in the court, or fulfillment of the obligation of the Local custom or legal obligations that live in society or social and mental rehabilitation. If the convicted person tries to avoid giving the compensation, the convicted person is not entitled to a reduction in the criminal term and does not get conditional released.